Management and Quality Management Principles in Ancient Greece and their Reflection Today - Aspridis, George; Poulianou, Louisa; Koukoumpliakos, Ioannis (International Conference on Business and Economics - Hellenic Open University, 2023)
The work of ancient Greek philosophers is, to say the least, timeless, multifarious and continues to be cited all over the world. Among all issues they highlighted the significance of management and the way in which the State as well as private affairs were organized. This proves that the prevailing view arguing that Management Science is the result of the industrial revolution and especially in Anglo-Saxon countries is not consistent with reality. In ancient Greece the structure of city-states has proven that an effective management function had been established, and by extension its application to all aspects of public life as well. Xenophon is considered by many the father of Management Science. The Oeconomicus by Xenophon refers to the art of household management, while the definition of management is introduced as well. The Nicomachean Ethics by Aristotle is widely considered a classical work which could be taught today in the Faculties of Management and Economics and particularly emphasizes on ethics, leadership and education. Aristotle laid the foundations of the scientific method and introduced the definition of Science. Through the Socratic method (maieutics), Socrates is considered the philosopher who established the concept of guidance, and regards management as a special skill, distinct from experience and knowledge. Plato referred to leadership and general culture as well as issues of ethics. Many political and military leaders (such as Cleisthenes, Miltiades, Thucydides, Solon and many others) engaged in state affairs management or took the lead in the military sector. The aim of the proposal under evaluation is to present the classical theories and the way they are incorporated into the modern management of both public and private sector in the era of globalization, multi-culturalism, diversity, electronic government and digital transformation. The proposal under evaluation has adopted the qualitative research method and specifically the tool of literature review. The aim is the holistic approach and analysis of the subject under research. Through the survey of literature, the researchers wish to present the timeless views on Management Science, as well as form new and modern ideas. For this reason, secondary publications relevant to the subject have been selected, such as the works of ancient Greek philosophers, studies, articles, reports, electronic books, texts from websites, etc. The conclusions of the proposal under evaluation are particularly significant and, whatever their utilization may be, can substantially contribute to the upgrading of Management Science in Greece. Ideally, these classical works could be taught in University Faculties at both undergraduate and postgraduate level. JEL Classifications: M00, N01 Key words: Quality Management, Administrative Science, Ethics, Management, Education